Patient Activation Among Prevalent Hemodialysis Patients: An Observational Cross-Sectional Study. (July 2022) - Hussein, Wael F; Bennett, Paul N; Sun, Sumi J; Reiterman, Marc; Watson, Emily; Farwell, Ian M; Schiller, Brigitte
Patient activation is the product of knowledge, skills, and confidence that enables a person to manage their own healthcare. It is associated with healthy behaviors and improved patient outcomes. We surveyed prevalent hemodialysis (HD) patients at 10 centers using the Patient Activation Measure 13-item instrument (PAM-13). Activation was reported as scores (0-100) and corresponding levels (1-4). Of 1149 eligible patients, surveys were completed by 925 patients (92% response rate). Mean age was 62 ± 14 years, 40% were female, median vintage was 41 (IQR 19-77) months, and 66% had diabetes. Mean PAM score was 56 ± 13, with 14%, 50%, 25%, and 10% in levels 1 to 4, respectively. In adjusted analysis, older age and having diabetes were associated with lower activation, whereas higher educational levels and female gender were associated with higher scores. Significant variation in activation was observed among participants from different centers even after adjustment for other variables. In conclusion, low activation is common among prevalent HD patients.